The phosphatidylinositol-5′ phosphatase synaptojanin1 limits integrin-mediated invasion of Staphylococcus aureus - Yong Shi; Petra Muenzner; Stefanie Schanz-Jurinka; Christof R. Hauck (Microbiology Spectrum, 2024)
ABSTRACTThe gram-positive bacterium Staphylococcus aureus can invade non-professional phagocytic cells by associating with the plasma protein fibronectin to exploit host cell integrins. Integrin-mediated internalization of these pathogens is facilitated by the local production of phosphatidylinositol-4,5-bisphosphate (PI-4,5-P2) via an integrin-associated isoform of phosphatidylinositol-5′ kinase. In this study, we addressed the role of PI-4,5-P2-directed phosphatases on internalization of S. aureus. ShRNA-mediated knockdown of individual phosphoinositide 5-phosphatases revealed that synaptojanin1 (SYNJ1) is counteracting invasion of S. aureus into mammalian cells. Indeed, shRNA-mediated depletion as well as genetic deletion of synaptojanin1 via CRISPR/Cas9 resulted in a gain-of-function phenotype with regard to integrin-mediated uptake. Surprisingly, the surface level of integrins was slightly downregulated in Synj1-KO cells. Nevertheless, these cells showed enhanced local accumulation of PI-4,5-P2 and exhibited increased internalization of S. aureus. While the phosphorylation level of the integrin-associated protein tyrosine kinase FAK was unaltered, the integrin-binding and -activating protein talin was enriched in the vicinity of S. aureus in synaptojanin1 knockout cells. Scanning electron microscopy revealed enlarged membrane invaginations in the absence of synaptojanin1 explaining the increased capability of these cells to internalize integrin-bound microorganisms. Importantly, the enhanced uptake by Synj1-KO cells and the exaggerated morphological features were rescued by the re-expression of the wild-type enzyme but not phosphatase inactive mutants. Accordingly, synaptojanin1 activity limits integrin-mediated invasion of S. aureus, corroborating the important role of PI-4,5-P2 during this process.IMPORTANCEStaphylococcus aureus, an important bacterial pathogen, can invade non-professional phagocytes by capturing host fibronectin and engaging integrin α5β1. Understanding how S. aureus exploits this cell adhesion receptor for efficient cell entry can also shed light on the physiological regulation of integrins by endocytosis. Previous studies have found that a specific membrane lipid, phosphatidylinositol-4,5-bisphosphate (PIP2), supports the internalization process. Here, we extend these findings and report that the local levels of PIP2 are controlled by the activity of the PIP2-directed lipid phosphatase Synaptojanin1. By dephosphorylating PIP2 at bacteria-host cell attachment sites, Synaptojanin1 counteracts the integrin-mediated uptake of the microorganisms. Therefore, our study not only generates new insight into subversion of cellular receptors by pathogenic bacteria but also highlights the role of host cell proteins acting as restriction factors for bacterial invasion at the plasma membrane.